Forest policy and politics in the Philippines the dynamics of participatory conservation - Bagadion, Benjamin C. Jr.; Utting, Peter; Contreras, Antonio P.; Leonen, Marvic M.V.F.; Malayang, Ben S. III; Severino, Howie G.; Vitug, Marites Danguilan (Quezon City Ateneo de Manila University Press, 2000)
'The essays in this collection originated under the auspices of an international research program on "Social and Political Dimensions of Environmental Protection Programs and Projects in Developing Countries" ... sponsored by the United Nations Research Institute for Social Development and supported financially by the Swiss National Science Foundation and the Swiss government's Agency for Development and Cooperation.' .. vii.
Towards Participatory Conservation: An Introduction / Peter Utting -- Chapter 1: Forest Policy and National Politics / Marites Danguilan Vitug -- Chapter 2: The Changing Role of Government in Forest Protection / Ben S. Malayang III -- Chapter 3: NGO Influence on Environmental Policy / Marvic M.V.F. Leonen -- Chapter 4: The Role of Local Stakeholders in Forest Protection / Howie G. Severino -- Chapter 5: Social and Political Determinants of Successful Community-Based Forestry / Benjamin C. Bagadion, Jr. -- Chapter 6: Rethinking Participation and Empowerment in the Uplands / Antonio P. Contreras -- Chapter 7: An Overview of the Potential and Pitfalls of Participatory Conservation / Peter Cutting.
Includes bibliographical references (pages 222-232) and index.
Keywords: Forest Policy -- Philippines; Forest Conservation -- Philippines -- Citizen participation